Using Blockchain in University Management Systems - et. al., Sura I. Mohammed Ali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
lockchain stores a series of transactions in form of a sequence of linked blocks. Hence, the concept of ledger is easily maintained. Transactions and interactions that take place among participants accessing the distributed and decentralized blockchain network are holding through ledger. In a student management system (SMS), vital information can be highly shared and well protected at the same time. This paper proposes a model for using blockchains to implement fully functional SMS that maintains students’ records, course registrations record and student marks. The proposed model adds more security via the use of hashing and data readily available with decentralized data storage. In addition, the use of ledger-based system to maintain SMS data introduces reliable and highly trusted model.